Improving Speaking Skills Through Acting-out Student-made Play Scripts - Moh. Hadiri (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2019)
This research is aimed at improving speaking skills of the eleventh graders ofSMK Hidayatul Mubtadien Sampang through acting-out student-made playscripts. This research employed Classroom Action Research. It is consists of 2cycles. Each cycle there were five meetings. Every cycle consists of fourphases in planning, implementing, observing, and reflecting. This research begunwith the preliminary study to find the problems. There were 8 students or 33.33%of students in the class who achieved KKM. The low scores are supportedfrom interview to the English teacher and some students. The result are the studentswere not motivated, lacked vocabulary, afraid and shy of making mistakes, notenthusiastic, bored, the students seldom to perform in speaking activities, teachercentered,and the students were passive in the teaching and learning process. Theresult of the study showed that the speaking test in cycle 1 were 13 students or54.17% and speaking test in cycle 2 were 20 students or 83.33% students in theclass who achieved KKM and the result of fieldnotes are: interested, enthusiastic,spirit, high motivation, active, brave, confident, and enjoy in speaking activities,and the result of questionnaire that the response of the students were strong andvery strong category. It can be concluded that their speaking skill improved.Keywords: speaking skill, acting play scripts, improving